2017
DOI: 10.1161/jaha.117.007409
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Female Sex Hormones Exacerbates Cerebrovascular and Cognitive Dysfunction in Aortic Banded Miniswine Through a Neuropeptide Y–Ca 2+ ‐Activated Potassium Channel–Nitric Oxide Mediated Mechanism

Abstract: BackgroundPostmenopausal women represent the largest cohort of patients with heart failure with preserved ejection fraction, and vascular dementia represents the most common form of dementia in patients with heart failure with preserved ejection fraction. Therefore, we tested the hypotheses that the combination of cardiac pressure overload (aortic banding [AB]) and the loss of female sex hormones (ovariectomy [OVX]) impairs cerebrovascular control and spatial memory.Methods and ResultsFemale Yucatan miniswine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 58 publications
4
27
0
Order By: Relevance
“…The CON group ingested a standard chow diet (5L80, Lab Diet; 3.03 kcal/g −1 ; carbohydrate: 71%; protein: 18.5%, and fat: 10.5%; 500 g/day), whereas the WD-AB group was fed a WD (1,000 g/day) high in fat, high-fructose corn syrup, and cholesterol (5B4L, Laboratory Diet; 4.14 kcal/g −1 ; carbohydrate: 40.8% [17.8% of total calories from high-fructose corn syrup]; protein: 16.2%; fat: 43%, 2% cholesterol wt/wt) as previously reported 13, 14, 15, 16, 17. At 6 months of age, aortic banding was used to induce HF as previously described 19, 20, 21, 22, 23, 25, 26, 27. A trans-stenotic systolic gradient of approximately 70 mm Hg (72 ± 2 mm Hg) was achieved under anesthesia using phenylephrine (intravenously 1 to 3 μg/kg/min) to maintain a distal peripheral vascular mean aortic pressure of approximately 90 mm Hg (87 ± 2 mm Hg) at a heart rate of 85 beats/min (84 ± 3 beats/min).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CON group ingested a standard chow diet (5L80, Lab Diet; 3.03 kcal/g −1 ; carbohydrate: 71%; protein: 18.5%, and fat: 10.5%; 500 g/day), whereas the WD-AB group was fed a WD (1,000 g/day) high in fat, high-fructose corn syrup, and cholesterol (5B4L, Laboratory Diet; 4.14 kcal/g −1 ; carbohydrate: 40.8% [17.8% of total calories from high-fructose corn syrup]; protein: 16.2%; fat: 43%, 2% cholesterol wt/wt) as previously reported 13, 14, 15, 16, 17. At 6 months of age, aortic banding was used to induce HF as previously described 19, 20, 21, 22, 23, 25, 26, 27. A trans-stenotic systolic gradient of approximately 70 mm Hg (72 ± 2 mm Hg) was achieved under anesthesia using phenylephrine (intravenously 1 to 3 μg/kg/min) to maintain a distal peripheral vascular mean aortic pressure of approximately 90 mm Hg (87 ± 2 mm Hg) at a heart rate of 85 beats/min (84 ± 3 beats/min).…”
Section: Methodsmentioning
confidence: 99%
“…A number of previous reports from our laboratory (and others) showed that Ossabaw swine, a unique translational large animal model genetically predisposed to obesity and metabolic derangement, do not develop HF from dietary intervention alone 10, 11, 12, 13, 14, 15, 16, 17. Furthermore, our laboratory previously published numerous studies that examined the impact of aortic banding alone (in the absence of comorbidities) on developing disease in a separate preclinical swine model of HF 18, 19, 20, 21, 22, 23, 24, 25, 26, 27. Thus, the primary goal of this study was to develop a swine model of experimental cardio-metabolic HF.…”
mentioning
confidence: 99%
“…Finally, old age represents a well-recognized POCD risk factor because of structural brain changes, dementia development, and lower cognitive reserves, as well as the limited recovery potential of the depleted brain [4,16]. Female sex is considered a predictor of POCD in the elderly population because of the role of estrogen in preserving brain homeostasis [27,79]. Genetic studies have revealed that certain combinations of C-reactive protein, interleukin-6, tumor necrosis factor-alpha and P-selectin polymorphisms, through modulation of the inflammatory response, contribute to the pathogenesis of POCD [1,27].…”
Section: Patient-related Risk Factorsmentioning
confidence: 99%
“…Aortic banding was also used to induce chronic pressure overload−induced HF in both 3- and 8-month-old Yucatan miniature swine using a 50- or 70-mm Hg systolic pressure gradient, respectively, placed on the ascending aorta over 6 months (see Figure 1 for surgical visualization) ( 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ). In this model, classic signs of experimental HF included increased LV brain natriuretic peptide mRNA levels and lung weight.…”
Section: Hf Induced By Pressure Overloadmentioning
confidence: 99%